Performance of a watergy audit on the submersible pumps of the Talamban Raw Water System in Cebu City - Reyes, Joseph Gerard T.; Odulio, Carl F.
As part of its efforts to promote awareness of energy-efficiency in water production and distribution companies in the Philippines, the Alliance to Save Energy (ASE) partnered with two provincial public water utility companies, one of which was the Metropolitan Cebu Water District in Cebu City. With the application of a methodology developed by the ASE and the Energy Research Institute (TERI) of India, a Watergy audit was performed on the submersible pumps of production wells within a selected raw water system of the MCWD, situated in the town of Talamban, Cebu City. The results of the audit led to the identification of opportunities for improvement of the pumps' performance and the formulation of recommended feasible measures toward attaining energy efficiency.
Keywords: Water efficiency -- Philippines (Cebu); Watergy audit; Specific energy consumption (SEC).